The Effect of Authentic Audio Materials on EFL Learners’ Listening Comprehension - Koliaei, Samira; Fatemipour, Hamidreza (Iranian Journal of Educational Sociology, 2022)
Purpose: This study explored the effect of authentic audio materials on enhancing listening comprehension of EFL learners. Methodology: To do the research, 120 EFL learners studying English in Setareh Language Institute in Tehran were selected. They took Oxford Placement Test and 60 advanced-level EFL learners as the research sample were randomly assigned into one experimental group and one control group. Then, both groups were given a version of TOEFL listening test as pretest before the treatment sessions. During the treatment, the experimental group received authentic listening materials. The listening sections were selected from the British radio on LBC. 97.3. The learners in control group received non-authentic listening materials from American English File4 which is a book with non-authentic listening texts. Having finished the treatment, the participants of the study were given another version TOEFL listening test as posttest. The data were analyzed through a series of paired and independent samples t-tests. Findings: The findings showed that authentic audio materials had a significant effect on listening comprehension of the EFL learners. Moreover, non-authentic audio materials had a positive effect on improving listening of the learners. However, the effect was not significant. Finally, the obtained data indicated that, there was a significant difference between authentic and non-authentic materials in improving the EFL learners' listening comprehension. Implication: Implications of the study suggest that authentic audio materials can enhance listening comprehension of Iranian advanced EFL learners.